2020
DOI: 10.4103/ijnmr.ijnmr_226_18
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' challenges in caring for an organ donor brain dead patient and their solution strategies: A systematic review

Abstract: Background: Caring for brain dead patient is one of the most troublous duties of an Intensive Care Unit (ICU) nurse. This study aimed to determine nursing challenges based on recent literature and identify the strategies to overcome these challenges. Materials and Methods: In this systematic review, the standard systematic review guideline of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was used with articles published in PubMed, Science D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Since the nurse's performance in process care can affect the health of the organ for patients on the waiting list for a transplant. [ 25 ] According to various studies, nurses have emotional, psychological, and supportive needs to care for the brain dead patient,[ 1 ] which should be taken into account which was not addressed in this model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the nurse's performance in process care can affect the health of the organ for patients on the waiting list for a transplant. [ 25 ] According to various studies, nurses have emotional, psychological, and supportive needs to care for the brain dead patient,[ 1 ] which should be taken into account which was not addressed in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Caring for brain dead patients is one of the hardest duties for nurses, particularly in intensive care units (ICUs). [ 1 ] The care process of brain dead patients involves several challenges, which often encompass its latent dimensions, urging researchers to conduct extensive research studies in this regard. Numerous qualitative and quantitative studies have been focused on the challenges and ambiguities of nurses in caring for brain dead patients and reporting issues, such as doubt of the brain death diagnosis,[ 2 3 ] ambiguity in understanding the concept of brain death,[ 4 5 6 ] challenges in caring for and communicating with the patients’ family,[ 7 8 9 ] religious, ethical, and cultural challenges regarding the acceptance of brain death and organ donation,[ 10 11 ] inadequate knowledge,[ 12 13 ] and lack of mental preparation for the care of potential organ donors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work of the NTC is key for the success of donation and transplant programs, as described in the Spanish model, and other models such as the United Kingdom, where the coordination of the process is carried out by nurses [25]. Within the nursing profession, this is an unknown job among peers, requiring specific training with professional independence within the health system [26]. The transplant coordinator is valued; however, a lack of professional definition and educational preparation has created confusion regarding the role [27].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the main candidates are nurses who are considered special units, working in emergency departments, ICUs, or operating rooms. In this sense, YazdiMoghaddam et al [26] reported that ICU nurses must have skills and knowledge that enable them to understand the concept and diagnosis of brain death, without any religious or cultural beliefs opposing organ donation, being well informed of the care process and how to interact with the families. Furthermore, Chen et al [36] described how nursing managers should have experience in the implementation of evidence-based practice.…”
Section: Discussionmentioning
confidence: 99%